Study the correlation between thyroid disorder and chronic kidney failure - Yosuf, Lina.M. (University of Thi-Qar Journal of Science, 2022)
Thyroid disorder and kidney function were once thought by specialists to be clinically negligible and spontaneous, but there have been many reports of elevated serum creatinine. hyperthyroidism patients.The present study was conducted through a number of hospitals in different regions of Iraq including Baghdad, Babylon, Najaf, Samawa and Maysan. The present study was conducted in the period from August Dec 2018. Samples were collected as 90 thyroid patients and 70 from CKD patients; A set of laboratory analyzes was conducted for the collected samples such as TSH hormon,Cr,urea,T3, andT4 hormone. Data of age, sex and chronic diseases was considered. The results showed there is a strong inverse relationship between TSH hormone and Cr at r=-0.5,p<0.01 for males categories 20-29Y, and40-49y. Moreover, it was found that there is a strong inverse relationship between TSH hormone and Cr at p<0.01 in hyperthyroidism male patients, and no significant correlation in hypothyroidism patients additionally, there is a strong inverse relationship between T4 hormone and Cr at r=-0.3 ,r=- 0.5 ,p<0.001 for males and females respectively in hypothyroidism patients in CKD patients. Forthermore, the results showed that there is a strong inverse relationship between TSH hormone and Cr at p<0.01 for males for ( 20-29,30-39,50-59)Y. This study recommends the need to perform kidney function tests for thyroid patients and treatment in the event of detect.